The struggle for Macedonia and the events in Thrace 1904-1908 (An Army History Directorate Publication, 2003)
The first edition of this project, published in 1979 in Greek, was awarded by the Athenian Academy Award. Its enriched reissue, by the title "The Macedonian Struggle and the events of Thrace", was released in 1998. The aforementioned publication refers to the history of Macedonia, by documenting the Greek ethnicity of the Macedonian people, presenting the Macedonian Issue during the 19th century and the armed forces of the Greek Army during the period 1904-1908. This publication is also enriched with appendices and tables translated in English.